Cane Ridge in context : perspectives on Barton W. Stone and the revival - Dunnavant, Anthony L., 1954- (Disciples of Christ Historical Society, 1992)
The nine chapters of the book introduce the reader to new insights in the place Barton Warren Stone has played in the life of the Stone-Campbell movement and the significance the Cane Ridge Revival and the Cane Ridge Congregation have had on our life as a people as a part of God's people. -- foreword.